The Development Model of the Merdeka Belajar Curriculum in Arabic Language Learning - Angelina Shondaqh; Firda Amalya Uliyani; Muhammad Yusril; Azwar Annas (El-Syaker : Samarinda International Journal of Language Studies, 2025)
In the increasingly evolving world of education, the need to create a more flexible and contextual learning system is becoming more urgent. The Merdeka Belajar Curriculum, which provides freedom and independence for students, presents itself as a solution to address these challenges. However, the implementation of the right learning model in the context of Arabic language learning remains an issue that requires further exploration. This study aims to identify the development models of the Merdeka Belajar Curriculum that are suitable for Arabic language learning. The research method used is library research with a qualitative descriptive design, where various literature and academic sources are analyzed to find the most effective model for implementing the Merdeka Belajar Curriculum in the context of Arabic language learning. The results show that the Problem-Based Learning (PBL) model is one of the most suitable models for implementation in Arabic language learning. This model demands that students think critically, creatively, and innovatively in solving problems related to the use of the Arabic language. Furthermore, this approach aligns with the Merdeka Belajar Curriculum concept, which provides students the freedom to explore and develop their understanding according to the needs and context of the learning process. By implementing Problem-Based Learning, it is expected that Arabic language learning will become more interactive, applicable, and foster students' independence in understanding and effectively using the Arabic language.